Kajian Penilaian Kinerja PDAM Kota Palangka Raya - Lolon, Antonius (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
The capacity of clean water production by PDAM Palangka Raya City is still in idle-capacity because from 255 l/s capacity installed is only used 179,5 l/s with the number of household water service connection is about 17.262 connection or same as 51,05% technical service area from its city population of 232.950 persons. Whereas, Directorate General of Human Settlements (Ditjen Cipta Karya), The Ministry of Public Works gives target that water services area should be in 100%. So that, it becomes a big challenge for The Government of Palangka Raya City, especially for PDAM, to improve its performance both technically and financially. The goal of this research is to review drinking water services system and to analyze performance of PDAM of Palangka Raya City by looking technical and non-technical data and also its institutional form from some indicators such as operational aspect, financial, administration, services, and human resources aspect that related to the effort to develop drinking water services. Research using quantitative methods with positivistic approach rationalistic. This research finds that performance of PDAM of Palangka Raya City, refers to Kepmendagri No. 47 Year 1999, has score 52,93 that categorized as